Comparative Assessment of Ohmic and Conventional Heating on Vitamin C, Antioxidant Activity, and Total Plate Count of Snake Fruit Juice (Salacca zalacca)” - Dea Arda Citra Putri Pratama; Luqman Agung Wicaksono; Dianita Kumalasari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study aimed to compare the effectiveness of ohmic heating and conventional heating on vitamin C retention, antioxidant activity, and total plate count (TPC) of snake fruit (Salacca zalacca) juice. The best ohmic heating treatment was determined using the De Garmo effectiveness index method and subsequently compared with conventional heating using an Independent Sample t-test. The best treatment was obtained at 80°C for 1 min (A3B1) with an effectiveness index value of 0.61. The results showed that the best ohmic heating treatment produced vitamin C content of 2.52 mg/100 mL, antioxidant activity of 65.88% inhibition, and TPC of 1.40 log CFU/mL. In comparison, conventional heating produced vitamin C content of 1.37 mg/100 mL, antioxidant activity of 62.22% inhibition, and TPC of 3.00 log CFU/mL. Statistical analysis indicated significant differences (p<0.05) in vitamin C, antioxidant activity, and TPC between ohmic heating and conventional heating. The results demonstrated that ohmic heating was more effective in retaining vitamin C and antioxidant activity while reducing microbial load than conventional heating. Therefore, ohmic heating has potential as an alternative pasteurization technology for producing high-quality and microbiologically safe snake fruit juice (Salacca zalacca).